Minimally Invasive Chevron Akin (MICA) Osteotomy for Severe Hallux Valgus - Gustavo A. Nunes MD; Kepler Carvalho MD; Gabriel F. Ferraz MD; Miguel V. Pereira Filho MD; Roberto Zambelli de A. Pinto MD (Foot & Ankle Orthopaedics, 2022)
Category: Bunion Introduction/Purpose: The minimally invasive Chevron Akin (MICA) osteotomy have been widely used treating hallux valgus (HV). The purpose of this study was to present a case series of patients with severe HV undergoing surgical treatment using the MICA procedure, and to evaluate the clinical and radiographic outcomes Methods: Sixty consecutive feet (52 patients) undergoing MICA for severe HV were included. Patients were assessed pre and postoperatively. Clinically evaluation was realized by visual analogue pain scale (VAS) and American Orthopaedic Foot & Ankle Society Score (AOFAS). Radiographic assessments included measurement of hallux valgus angle (HVA), intermetatarsal angle (IMA), metatarsal (MT) length and plantar offset of MT head. Results: The mean age was 59.9 years and follow-up were 18.5 months. The average AOFAS increased from 41.2 to 90.9 points and the VAS decreased from 8.1 to 1.3 at the last follow up. Average HVA decreased from 41.2° to 11.6° and IMA reduced from 17.1° to 6.8°. Average shortening of the first metatarsal and the plantar offset of MT head was 3.9 mm and 2.8 mm respectively. There was significant improvement (p<0.001) in all clinical and radiographic parameters (p<0.001). The most observed complication was hardware discomfort, observed in four feet (6.6%). Conclusion: The MICA technique is a safe and reproducible method to treat severe HV.